Effects of copper nanoparticle treatment on the properties of hybrid corn seeds - Liziane Cassia Carlesso; Giovana Feltes; Cristiano Reschke Lajus; Carina Rossoni; Rosicler Colet; Clarice Steffens; Juliana Steffens (Acta Scientiarum. Agronomy, 2025)
Corn (Zea mays L.), a vital crop economically and nutritionally, benefits from advancements like copper (Cu) nanoparticles, which are engineered to enhance crop growth and grain quality. This study aimed to assess the morphological, physical, chemical, and quality attributes of various corn hybrids (HB 01: 22S18 TOP2®; HB 02: 20A30 VIPTERA®; HB 03: 20A80 TOP2®; HB 04: 22S18 TOP3®, and HB 05: 20A20 TOP2®) treated with copper nanoparticles (900 mg of Cu L-1). Hybrid HB 04: 22S18 TOP3® exhibited the highest levels of protein, lipids, fiber, and phosphorus, though calcium levels were comparable to other hybrids (p > 0.05). Fatty acid and amino acid profiles remained unchanged. Hybrids not treated with Cu nanoparticles had higher pH levels. The Cu nanoparticles primarily altered the surface, not the interior, of the seeds, with HB 02: 20A30 VIPTERA® showing the highest Cu content. Overall, Cu nanoparticles preserved the physical and chemical properties of the corn grains, confirming their viability for seed treatment.